Prevalence and risk factors of physical inactivity among middle-aged and older Chinese in Shenzhen: a cross-sectional study. Issue 10 (15th October 2018) - Zhou, Yanfeng; Wu, Jiang; Zhang, Shenchao; Yan, Shijiao; He, Liping; Mkandawire, Naomie; Song, Xinyue; Gan, Yong; Li, Wenzhen; Yang, Tingting; Li, Jing; Zeng, Xiaozhou; et al.
Abstract : Objective: Investigations on physical inactivity are common around the world; however, little is known about the status of physical inactivity in mainland China. The aim of this study was to examine the prevalence and risk factors associated with physical inactivity in Shenzhen in Southern China. Design: A community-based, cross-sectional study. Setting: A multistage-stratified, random cluster survey was conducted in Xixiang Street, Bao'an District of Shenzhen in Southeast China. Participants: 3920 adults aged 40 years or more were recruited to the study and completed the International Physical Activity Questionnaire Short Form between 1 March 2015 and 30 July 2016. Main outcome measures: Physical inactivity was defined as engaging in physical activity levels insufficient to reach the current guidelines. Bivariate and multivariate analyses were undertaken to assess the prevalence and risk factors associated with physical inactivity. Results: The prevalence of physical inactivity was 63.1% for all participants, 63.9% for women and 61.9% for men, respectively. Participants who were older (OR=1.31, 95% CI 1.11 to 1.54), who were female (OR=1.22, 95% CI 1.04 to 1.43), who had higher education experience (OR=1.38, 95% CI 1.19 to 1.61), who are under economic pressure (OR=2.17, 95% CI 1.48 to 3.17), who ever smoked a cigarette (OR=1.44, 95% CI 1.13 to 1.82) and drank alcohol (OR=1.42, 95% CI 1.14 to 1.77), and participants in the lowest body mass index category (OR=1.40, 95% CI 1.03 to 1.89), were more likely to report physical inactivity. Conclusions: These findings indicate that physical inactivity is prevalent in Southern China. Interventions and programmes aimed at increasing physical activity among middle-aged and older Chinese adults may also be tailored to participants under economic pressure and those with unhealthy behaviours such as smoking and drinking.